Financial Intermediation by Microfinance Banks in Rural Sub-Saharan Africa: Financial Intermediation Theoretical Approach - Bongomin, George Okello Candiya; Yosa, Francis; Lubega, Joseph Baleke Yiga; Yourougou, Pierre; Amani, Alain Manzi (Journal of Comparative International Management)

(untitled) (Management Futures, 2021)
Premised on Meta analysis of financial intermediation theory by Gurley and Shaw (1960), Leland and Pyle (1977), Diamond and Dybvig (1983), Allen and Santomero (1996), Scholtens and van Wensveen (2000), the main purpose of this study is to test for the predictive power of each of the dimensions of financial intermediation of market penetration and quality of financial services on financial inclusion of the poor by microfinance banks in rural sub-Saharan Africa grounded on the financial intermediation theory. This study adopted a cross-sectional research design and data were collected from 400 poor households located in rural Uganda. The data were analyzed using ordinary least square hierarchical regression (OLS) in SPSS (statistical packages for social sciences) to generate the explanatory power of each of the dimensions of financial intermediation on financial inclusion based on coefficient of determination (R²). In addition, results from analysis of variances (ANOVA) were also generated to establish the differences in the perceptions of the poor towards being financially included through financial intermediation. The results revealed that market penetration and quality of financial services as dimensions of financial intermediation significantly explains 22 percent of the variation in financial inclusion of the poor in rural Uganda. Additionally, when individual effects were considered, both market penetration and quality of financial services had significant and positive effects on financial inclusion of the poor in rural Uganda. Accordingly, our study contributes and recommends specific policies toward the role of financial intermediaries in financial deepening, especially in rural sub-Saharan Africa where there are limited presence of traditional banking structures to serve the unbanked rural poor households.